Realitas Pemikiran Islam: Moderat-Puritan - Djami’atul Islamiyah (Millati: Journal of Islamic Studies and Humanities, 2017)
The distinction of Khaled Abou El Fadl, the moderate-puritan is actually only one of the distinction models of Islam. Other distinctions include “liberal-conservative” from Ann Elizabeth or the “Islamic and Islamic fundamentalism” from Bassam Tibi. The emergence of these distinctions is related to differences in understanding the interaction with non-Muslims and the concept of salvation in the context of religious plurality. It is hard to imagine that they both read and interpret the same source (the Qur’an) but in terms of the output interpretation, these two groups are very diametrical and incompatible. This raises a question of what their premises and logic are in order to make a difference in describing the will of God. If the difference is only on the level of discourse, it might not be too worrisome. The problem is the difference in the interpretation implied on the rise of violence in the name of religion. So aside from causing negative image on Islam as a violent and intolerant religion, as well as the word “Islam” has generated negative sentiments in various countries, starting from a nonchalant attitude that has a lot of suspicion to fear and hatred. El Fadl realizes that the Islamic world can not be reduced in these two categories only. The reality of modern Islam is much more complex and there is another orientation of thought. But at least this distinction can illustrate the existence of schism in Islamic thought between moderate Islam and puritan Islam lately.